Determinant Factors of Personal Innovativeness in Information Technology of Ride-Hailing New Brand: The Role of Gender - Lattu, Arny; Maulana, Agung (CV. AFDIFAL MAJU BERKAH, 2023)
The objective of this study is to examine the influence of electronic word of mouth (E-WOM), social influence (SI), and perceived system and service quality (PSSQ) on personal innovativeness in information technology (PIIT) with respect to the adoption of a novel ride-hailing application brand. The research object selected for this study is the MAXIM and InDriver application, which represents a new brand in the market. The present study employed a questionnaire-based survey to gather data from a sample of 553 individuals who identified as users of either MAXIM or InDriver and who belong to the Z generation. The study employed the use of structural equation modeling (SEM) techniques, specifically utilizing the SMART-PLS software version 3. The findings of the study indicate that electronic word-of-mouth (E-WOM), social influence, and perceived system and service quality have a positive impact on an individual's inclination to adopt a new brand of ride-hailing application. . Furthermore, the findings indicate that gender impacts the propensity to adopt a new brand of ride-hailing application, with men exhibiting a greater inclination towards innovative experimentation than women.